Sperm subpopulations in chilled rabbit semen with different diluents - Suárez A., Camila (2021)
The reproductive activity of various species of mammals is influenced by the sperm subpopulations of their ejaculates. These subpopulations differ in the motility and kinetic characteristics of the sperm and have been related and classified according to their capacity for the fertilization process. The objective of this research was to evaluate the effect of the composition of the semen diluent on the sperm subpopulations of the chilled rabbit semen. The semen of 10 rabbits of the Californian breed (three ejaculated per animal) was obtained. Each ejaculate was divided into four aliquots, which were diluted in one of four diluents, whose basic composition consisted of T1: skim milk and sugars; T2: dextrose, sodium citrate and potassium acetate; T3: sodium caseinates, phosphates and sugars; and T4: tris-citric acid and egg yolk. Each aliquot was kept refrigerated at 16 °C for 72 h. Immediately after dilution and every 24 h, the distribution of four sperm subpopulations was evaluated using a computerized system: Type A (rapid progressive spermatozoa), Type B (rapid spermatozoa and medium progressive spermatozoa), Type C (medium spermatozoa and slow spermatozoa) and Type D (static spermatozoa). The data were analyzed using the PROC GLM and Tukey's HSD test of the SAS v. 9.2. It was found that T1 and T3 produced superior results for curvilinear velocity (VCL), straight line velocity (VSL), average path velocity (VAP) and amplitude of lateral head displacement (ALH) of sperm refrigerated for 24 and 48 hours (p<0.05), while T2 and T4 produced an increase in the beat cross frequency (BCF) (p<0.05). It is concluded that the composition of the diluent influences the distribution of the sperm subpopulations of the refrigerated rabbit semen, by generating changes in the progressivity and kinetics of the sperm.